Analysis Of Leadership, Work Ability And Work Discipline On Employee Performance At PT Aditya Mandiri Sejahtera - Silaban, Hesra Maria; Kemalasari, Nuraini (Universitas Dehasen Bengkulu, 2025)
This research was conducted at PT. Aditya Mandiri Sejahtera which is engaged in the fashion retail sector with the aim of the research to determine the effect of leadership, work ability and work discipline partially and simultaneously on employee performance in carrying out tasks. The population is employees working in the company as many as 65 employees and sampling with saturated samples so that the number of samples is 65 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption tests and hypothesis tests. The results of the study show that leadership, ability to work and work discipline partially and simultaneously have a positive and significant effect on employee performance at PT. Aditya Mandiri Sejahtera. There is a very strong correlation between leadership, work ability and work discipline with employee performance in carrying out tasks in the company. Employee performance in the company can be explained by leadership, work ability and work discipline by 86% and the remaining 14% can be explained by other variables not studied such as training, compensation and career development and so on.